2019
DOI: 10.3390/ma12172803
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Single (AlSi7/SiCp, AlSi7/GCsf) and Hybrid (AlSi7/SiCp + GCsf) Composite Layers Formed in Sleeves via Centrifugal Casting

Abstract: When designing the composition and structure of a composite material intended for tribological cooperation, many external and structural factors must be considered. The aim of this research was to compare the tribological properties (wear resistance and friction coefficient) of AlSi7Mg1Sr0.03/SiCp and AlSi7Mg1Sr0.03/GCsf single-reinforced composite layers with AlSi7Mg1Sr0.03/SiCp + GCsf hybrid composite layer formed in sleeves via vertical centrifugal casting. Profilometry enabled quantitative and qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Similar results were obtained and reported in the present authors' papers, such as e.g., [23][24][25]. It was shown that the use of hybrid suspensions of Al/SiC p + GC p type enables obtaining cylindrical centrifugal castings with two functional composite layers of different thickness and favorable tribological properties correlated with the type, share (V p ), and diameter (D p ) of reinforcing particles.…”
Section: Introductionsupporting
confidence: 91%
“…Similar results were obtained and reported in the present authors' papers, such as e.g., [23][24][25]. It was shown that the use of hybrid suspensions of Al/SiC p + GC p type enables obtaining cylindrical centrifugal castings with two functional composite layers of different thickness and favorable tribological properties correlated with the type, share (V p ), and diameter (D p ) of reinforcing particles.…”
Section: Introductionsupporting
confidence: 91%
“…In the first stage, composite suspensions were prepared by stir casting in an autoclave furnace with a moving graphite stirrer system, according to the procedure described in [ 7 , 14 ]. In the second stage, heated composite suspension was cast into the rotating mold (d = 60 mm; ω = 3000 rpm), according to the method described in previous own works [ 12 , 13 ]. An example of a cast of composite sleeves and its microstructure in the outer area is shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Aluminum matrix composites reinforced by silicon carbide (SiC) are a material solution successfully applied in the automotive field [ 8 , 9 , 10 ]. The popularity of these composites is due to a number of their properties, such as wear resistance, stiffness, compressive strength, low density, low coefficient of thermal expansion, good casting properties, and low production costs [ 11 , 12 ]. This kind of composite is widely used in tribological conditions where material is constantly subjected to variable loads and high-temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the liquid matrix technology, there are two fundamentally varying methods of composite production, such is direct methods, and indirect methods [2,3,8,28,30,32,37,38,[44][45][46][47].…”
Section: Division Of Composite Materialsmentioning
confidence: 99%
“…Composite materials can be divided depending on the production method, intended use, technological properties, and depending on the matrix as well. Metal matrix composites are currently produced with a variety of methods, which include but are not limited to [ 2 , 3 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]: Liquid matrix technologies (only these will be the subject of this paper because it concerns defects of castings); Deformation technologies, i.e., those that use plastic processing methods; Sinter technologies. …”
Section: Classification Of Metal Matrix Compositesmentioning
confidence: 99%